2015
DOI: 10.1016/j.cplett.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Fluorenyl porphyrins for combined two-photon excited fluorescence and photosensitization

Abstract: The two-photon absorption (2PA), the luminescence and the photosensitization properties of porphyrin-cored fluorenyl dendrimers and meso-substituted fluorenylporphyrin monomer, dimer and trimer are described. In comparison with model tetraphenylporphyrin, these compounds combine enhanced (non-resonant) 2PA cross-sections in the near infrared and enhanced fluorescence quantum yields, together with maintained singlet oxygen generation quantum yields. "Semi-disconnection" between fluorenyl groups and porphyrins (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 48 publications
3
32
0
Order By: Relevance
“…d Literature value of φ F = 0.23 (± 0.03) determined via the comparative method using chlorophyll in diethylether as standard [29]. e In CH 2 Cl 2 [22,25].…”
Section: Absorption Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…d Literature value of φ F = 0.23 (± 0.03) determined via the comparative method using chlorophyll in diethylether as standard [29]. e In CH 2 Cl 2 [22,25].…”
Section: Absorption Propertiesmentioning
confidence: 99%
“…We also observed that the various fluorene-containing dendrons act as light-harvesting antennae, before transferring their energy to the central porphyrin core. Although the emission quantum yields are slightly diminished compared to that for the smaller TFP reference compound [20], we showed that their brightness was much improved [26].Following our initial goal to further improve the luminescence quantum yield of the photosensitizers with flexible arms [22,23,25], we now wondered about the impact of replacing the porphyrin central core by a phthalocyanine ring. Based on literature reports, this tetrapyrrolic unit should be able to photosensitize oxygen with an efficiency similar to that of the meso-tetraarylporphyrin core once metalated by Zn(II) [27], but should also present a significantly improved fluorescence quantum yield [7].…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…It should be emphasized that even higher TPAc ross-sections have already been obtained with other porphyrin systems, [23] exhibitingm ore efficient conjugation between the subchromophoric moieties, but generally along with strong modifications of the other photophysical properties, which limit their interest for theranostic applications.I ndeed, such compounds usually exhibit am odest to negligible fluorescence, as well as interfering residual one-photon absorption (OPA), which leads to the loss of some advantages of selectiveT PA,m ainly the 3D resolution. In contrast, fluorenyl-porphyrin dendrimers exhibit an improved trade-off [24] between selective( non-resonant) TPA cross-sectionsand fluorescenceproperties.…”
Section: Two-photon Absorptionmentioning
confidence: 99%